METHODOLOGICAL FEATURES OF TEACHING CHEMISTRY IN DISTANCE LEARNING CONDITIONS (Education in the 21st Century, 2025)
The article examines the methodological features of organizing distance learning in chemistry in modern conditions. A comprehensive analysis of the digital educational environment is presented, including an overview of platforms, tools, and resources for teaching chemistry in an online format. Special attention is paid to practical aspects of organizing virtual chemical experiments and various forms of educational activities. Effective methodological techniques for increasing student engagement and maintaining their motivation in distance learning conditions are proposed. The results of an experimental study confirming the effectiveness of the developed methodology are presented. Based on the obtained data, practical recommendations for improving the process of distance learning in chemistry are formulated.
Keywords: chemistry teaching methodology; digital educational environment; digital tools; distance learning; educational technologies; online learning; pedagogical experiment; virtual chemical experiment